Eksistensi Owabong Dalam Perspektif Semangat Enterpreneurship Pemerintah Daerah - Suyudi Suyudi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2010)
Strategic issues of the local autonomy in local autonomy era makes local governments must be creative and innovative ways to develop income sources to increase Local Original Income (PAD). That's needed the entrepreneurship spirit of local government. This study aims to analyze the existence Owabong terkiat with one application of the principles of reinventing government, namely the Government of Entrepreneurship. Research design using case studies based on secondary data. Methods of data collection using the documentation. Analysis of data using qualitative analysis. The results showed that the presence of Owabong is empirical evidence of entrepreneurial spirit owned by Government of Purbalingga Regency. Government of Purbalingga Regency seeks to explore and optimize local assets held for further developed to become a real source of local revenue. Owabong positioned as a regional asset that profit-oriented in order to increase local income. This effort has positive results, which can be seen from the development Owabong as a source of revenue for the Government of Regency Purbalingga.